Association between GH (g.1456_1457insT), GHRH (g.4474 C>A), and Pit-1 (g.244G>A) Polymorphisms and Lactation Traits in Holstein Friesian Cattle - Anggraeni, A.; Sumantri, C.; Saputra, F.; Praharani, L. (Tropical Animal Science Journal, 2020)
Lactation traits are controlled by many genes, among others, potentially by growth genes. This research was conducted to study genetic polymorphisms of GH, GHRH, and Pit-1 genes and associations of GH (g.1456_1457 InsT), GHRH (g.4474 C>A), and Pit-1 (g.244 G>A) genotypes with milk yield and quality in Holstein Friesian (HF) cattle. Genotyping was conducted for HF dairy cows raised by small farmers from North Lembang (SF-NL) (98 heads) and South Lembang (SF-SL) (95 heads), and also from Cikole Dairy Cattle Station (CDCS) (82 heads) in Lembang, West Java, Indonesia. Progeny tested of HF bulls (17 heads) from LAIC (Lembang Artificial Insemination Center) in West Java and from SAIC (Singosari AIC) (32 heads) in East Java were also genotyped. Effects of genotypes on test day milk yield, fat content, and SNF content were analyzed by General Linear Models. The GHRH g.4474 C>A SNP and Pit-1 g.244 G>A SNP generated high frequencies of C allele to A allele, while the two allelic frequencies of the GH g.1456_1457 InsT varied. Compared to the AA and AC genotypes, the CC genotype of the GH gene resulted higher test day milk yield (p